Teachers' reflections on proposals for change in situated teamwork. Issue 4 (4th July 2021) - Lysberg, Julie; Rønning, Wenche
ABSTRACT: The purpose of this paper is to investigate what characterizes individual teachers` reflections on proposals for change in situated teamwork sessions and discuss the potential for professional development that lies in teachers' reflections. The teamwork sessions take place in the context of school-based professional development. Stimulated recall interviews (SRI) with teachers commenting on video recordings from their participation in teamwork form the empirical basis for the research. The sample consists of 17 teachers representing four teacher teams from different schools. We identified three primary types of reflection on proposals of change – comment and describe, extend and exemplify, and critical exploration. In the last type of reflection, when teachers critically explore, reflect and problematize existing practices whilst watching critical incidents that contain proposals for change, we identified tensions arising. The tensions emerged between teachers' established practices grounded in national regulations (ex. national tests, exams, documentation) and their basic assumptions, values, and beliefs.